(untitled) (Cultura Económica, 2019)
In 1947 a group of American Catholic intellectuals gathered in Uruguay signed the Declaration of Montevideo. In it, the signatories pledged to influence on their countries politics on the basis of the Social Doctrine of the Church. In subsequent years, many of them held important government positions in both the Executive branch and in the Legislative branch. In the Argentine case, however, the matter was not easy. On the return of the delegates, it began a complex controversy around the present social economic principles in the Declaration, among them the problem of the meaning of the notion of social justice and its relation to the capitalist economy. This article seeks to examine the main positions that were generated in this debate, showing the efforts of each of these authors to specify the content of this idea and its relation to economic and social sciences. Particularly, the challenge they had to face was to address to what extent the Christian social thought was consistent with the capitalist economy that, after the Second World War, appeared as the only possible economic model against communism, or if it was necessary to think of a better alternative.